2021
DOI: 10.1016/j.jlr.2021.100066
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin inhibits POVPC-mediated induction of endothelial-to-mesenchymal cell transition

Abstract: Endothelial-to-mesenchymal transition (EndMT), the process by which an endothelial cell (EC) undergoes a series of molecular events that result in a mesenchymal cell phenotype, plays an important role in atherosclerosis. 1-Palmitoyl-2-(5-oxovaleroyl)-sn-glycero-3-phosphocholine (POVPC), derived from the oxidation of 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphatidylcholine, is a proinflammatory lipid found in atherosclerotic lesions. Whether POVPC promotes EndMT and how simvastatin influences POVPC-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…A study by (25) has shown that simvastatin can inhibit EndMT via upregulation of KLF4/miR-483 axis in HUVECs. Additionally, simvastatin attenuated 1-Palmitoyl-2-(5-oxovaleroyl)-sn-glycero-3-phosphocholine (POVC) inducing EndMT, by suppressing oxidative stress and TGF-β/SMAD signaling, suggesting that simvastatin could potentially be used in treating atherosclerosis (97). Altogether, these findings suggest the therapeutic potential of EndMT disruption in atherosclerosis.…”
Section: Preventing Endmt As a Potential Approach To Treat Atherosclerosismentioning
confidence: 87%
“…A study by (25) has shown that simvastatin can inhibit EndMT via upregulation of KLF4/miR-483 axis in HUVECs. Additionally, simvastatin attenuated 1-Palmitoyl-2-(5-oxovaleroyl)-sn-glycero-3-phosphocholine (POVC) inducing EndMT, by suppressing oxidative stress and TGF-β/SMAD signaling, suggesting that simvastatin could potentially be used in treating atherosclerosis (97). Altogether, these findings suggest the therapeutic potential of EndMT disruption in atherosclerosis.…”
Section: Preventing Endmt As a Potential Approach To Treat Atherosclerosismentioning
confidence: 87%
“…Indeed, previous work has linked EndMT to neointimal hyperplasia ( Chen et al, 2015 ; Moonen et al, 2015 ), increased leukocyte migration ( Evrard et al, 2016 ), lipid uptake by lesional macrophages ( Chen et al, 2019 ), and oxidative stress ( Evrard et al, 2016 ) in the developing plaque ( Figure 1 ). Moreover, statin therapy ( Li Y. et al, 2021 ), histone deacetylase inhibitors ( Chen et al, 2021 ), and microRNA inhibition ( Wu et al, 2021 ) have recently been investigated as potential strategies for limiting EndMT, the latter of which was observed to reduce plaque formation in atherosclerotic mice.…”
Section: Endothelial Cell Plasticity Contributes To the Atherosclerotic Disease Processmentioning
confidence: 99%
“…It has been shown the truncated Ox-PAPCs, including POVPC and PGPC, can induce vascular leaking and exacerbate inflammation, due to their direct pro-inflammatory effects on both endothelial cell and macrophages ( 24 , 34 , 35 ). The deleterious effects of POVPC on endothelial function have been highlighted for decades in cardiovascular diseases ( 36 38 ). Therefore, the variety of POVPC function could be an explanation for why HDL POVPC was not significantly correlated with these SOFA scores, plasma CRP, and other pro-inflammatory cytokines enhanced in septic patients.…”
Section: Discussionmentioning
confidence: 99%